(untitled) (Journal of Contemporary Philology, 2018)
The paper presents the results of the contrastive analysis between present perfect simple and present perfect continuous in English, and the perfect in Macedonian in order to determine the similarities and differences between these tenses . The analysis is based on data from various sources, as well as on the data from The Macedonian English Learner Corpus (MELC), which is an electronic database containing texts produced by learners of the English language. The results of the contrastive analysis provide new insights useful in English language teaching. Relying on the assumption that the Macedonian language influences the acquisition process of present perfect simple and present perfect continuous, this article points out the typical problems that Macedonian learners are expected to face while studying the two categories under examination.